2008
DOI: 10.1111/j.1460-9568.2008.06543.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress reduces postnatal neurogenesis in rats selectively bred for high, but not low, anxiety: possible key role of placental 11β‐hydroxysteroid dehydrogenase type 2

Abstract: Prenatal stress (PS) produces persistent abnormalities in anxiety-related behaviors, stress responsivity, susceptibility to psychopathology and hippocampal changes in adult offspring. The hippocampus shows a remarkable degree of structural plasticity, notably in response to stress and glucocorticoids. We hypothesized that PS would differentially affect hippocampal neurogenesis in rats selectively bred for genetic differences in anxiety-related behaviors and stress responsivity. Pregnant dams of high anxiety-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 74 publications
5
72
2
1
Order By: Relevance
“…It is a general belief that hippocampal neurogenesis is enhanced by antidepressant drugs (Santarelli et al 2003; reviewed by Malberg and Schechter 2005;Tanti and Belzung 2010). However, there are exceptions (Marlatt et al 2010) and, in addition, the action of antidepressants on neurogenesis might be critically influenced by age, gender, and stress context (Oitzl et al 2000;Navailles et al 2008;Lucassen et al 2009;2010a;Oomen et al 2009Oomen et al , 2010. In a mouse model of depression induced by chronic corticosterone treatment, only some "therapeutic effects" of fluoxetine are neurogenesisdependent (David et al 2009), and there is also evidence that antidepressants retain their "therapeutic" efficacy when neurogenesis is blocked by a cytostatic drug (Bessa et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…It is a general belief that hippocampal neurogenesis is enhanced by antidepressant drugs (Santarelli et al 2003; reviewed by Malberg and Schechter 2005;Tanti and Belzung 2010). However, there are exceptions (Marlatt et al 2010) and, in addition, the action of antidepressants on neurogenesis might be critically influenced by age, gender, and stress context (Oitzl et al 2000;Navailles et al 2008;Lucassen et al 2009;2010a;Oomen et al 2009Oomen et al , 2010. In a mouse model of depression induced by chronic corticosterone treatment, only some "therapeutic effects" of fluoxetine are neurogenesisdependent (David et al 2009), and there is also evidence that antidepressants retain their "therapeutic" efficacy when neurogenesis is blocked by a cytostatic drug (Bessa et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…A variety of different hormonal and environmental exposures regulate the genesis of new cells, which ultimately may also influence the electrophysiological characteristics of the target circuits. Early life stress exposures, either prenatal (Coe et al 2003;Lemaire et al 2000;Lucassen et al 2009;Mandyam et al 2008) or postnatal (Lemaire et al 2006;Mirescu et al 2004), have been shown consistently to reduce neurogenesis in the adult dentate gyrus in rodents and non-human primates, an effect which may be mediated via corticosterone (Mirescu et al 2004). The consequences of reduced neurogenesis in the dentate gyrus on the electrophysiological properties of this structure, and those it connects to, may be related to the observed effects of early life stress on such outcomes as hippocampal LTP and LTD, as described earlier.…”
Section: Gaba a Receptorsmentioning
confidence: 96%
“…Rodent studies over the past decades have shown that neurogenesis appears to be very sensitive to stress, particularly when stress occurs during the perinatal period (Korosi et al 2012). Also, perinatal stress can induce reductions in AN in the offspring (Lemaire et al 2000;Coe et al 2003;Lucassen et al 2009) (although exceptions have been reported [Tauber et al 2008]). Such reductions may, in part, occur through epigenetic modifications, often in a sex-dependent manner (Lucassen et al 2013b).…”
Section: Long-lasting Effects Of Perinatal Stress Exposurementioning
confidence: 99%